Non-random distribution of 17 Y-chromosome STR loci in different areas of Sardinia. (May 2015) - Robledo, R.; Mameli, A.; Scudiero, C.M.; Vona, G.; Corrias, L.; Bachis, V.; Culigioni, C.; Calò, C.M.
Highlights: Sardinians are well differentiated from other Italian and Mediterranean populations. We detected genetic heterogeneity in Sardinia when microareas were analyzed. A Sardinia-own database, organized by small areas, should be created. Abstract: Allele frequencies of 17 Y-chromosome short tandem repeat (STR) loci, included in the AmpFlSTR ® Y-FilerTM amplification kit, were analyzed for the first time in different samplings ( N  = 268) from Sardinia, Italy. Samples were collected from three isolated populations ( N  = 139) and three open populations ( N  = 129). A total of 230 unique haplotypes were detected; the observed haplotype diversity and discrimination capacity were 0.998 and 0.858, respectively. The data presented confirm that Sardinian population is well differentiated from other Italian and Mediterranean populations. Although regarded as a homogeneous population, substantial heterogeneity was detected when Sardinian isolated villages or microareas were analyzed. Our results highlights the importance of building a Sardinia-own database, organized by small areas, as a powerful tool for both forensic applications and population genetics studies.